High-fat Diet Mediates Anxiolytic-like Behaviors in a Time-dependent Manner Through the Regulation of SIRT1 in the Brain. (21st February 2018) - Xu, Liu; Xu, Shuang; Lin, Lifang; Gu, Xi; Fu, Congcong; Fang, Yingying; Li, Xiaowen; Wang, Xuemin
Highlights: 4-Week HFD feeding induced anti-anxiety behaviors, but 12-week HFD feeding didn't show anxiolytic effect. SIRT1 expression decreased in the mPFC and the amygdala of 4-week HFD-fed mice. SIRT1 activator, resveratrol, reversed anxiolytic behaviors in 4-week HFD-fed mice. SIRT1 decrease was not observed in the mPFC or the amygdala of 12-week HFD-fed mice. The SIRT1 inhibitor, EX527, did not show any anxiolytic effect in HFD-fed mice. Abstract: The consumption of a high-fat diet (HFD) and obesity have been associated not only with metabolic diseases but also with neuropsychiatric diseases, such as depression and anxiety. However, results on the effects of an HFD on anxiety are controversial, since both anxiogenic and anxiolytic effects have been reported. In this study, we evaluated the effects of both short- and long-term intake of an HFD on anxiety-like behaviors. To explore the impact of time on the association between an HFD and anxiety, mice were fed with an HFD for 4 weeks or 12 weeks. Compared with control-diet mice, mice given an HFD for 4 weeks displayed anxiolytic-like behaviors. At the same time, we observed decreased SIRT1 expression in the mPFC and the amygdala of HFD-fed mice. Moreover, resveratrol, an activator of SIRT1, reversed the anxiolytic-like behaviors in HFD-fed mice. However, after 12 weeks of consuming a high-fat diet, mice did not exhibit any anti-anxiety behavior or further decreases in SIRT1 expression in the aforementioned brain regions compared with CD-fed mice. When EX-527, a SIRT1 inhibitor, was intraperitoneally injected, we observed anxiolytic effects in the CD-fed mice but not in the 12-week HFD-fed mice. Collectively, our data demonstrate that exposure to a short-term HFD can induce anxiolytic behaviors, which may be associated with decreased SIRT1 in the mPFC and the amygdala. However, this effect is abolished when the high-fat diet is extended to 12 weeks. Together, these results demonstrate that SIRT1 plays an essential role in regulating mood-related behaviors in HFD-fed mice.